2003
DOI: 10.1086/374949
|View full text |Cite
|
Sign up to set email alerts
|

Radial Velocity Studies of Close Binary Stars. VIII.

Abstract: Radial-velocity measurements and sine-curve fits to the orbital velocity variations are presented for the seventh set of ten close binary systems: V410 Aur, V523 Cas, QW Gem, V921 Her, V2357 Oph, V1130 Tau, HN UMa, HX UMa, HD 93917, NSV 223. All systems, but three (V523 Cas, HD 93917, NSV 223), were discovered photometrically by the Hipparcos mission. All systems are double-lined (SB2) binaries and all, but the detached, very close system V1130 Tau, are contact binaries. The broadeningfunction permitted improv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
62
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 15 publications
13
62
1
1
Order By: Relevance
“…Finally, we note that if the light center velocities are applied without corrections, both semiamplitudes become 1.1 km s −1 smaller than listed in Table 7, and the derived masses become about 0.03 M lower. Our results differ slightly from those by Rucinski et al (2003), K p = 160.11 ± 0.74 km s −1 , K s = 147.21 ± 0.63 km s −1 , and γ = −12.74 ± 0.46 km s −1 , and are more accurate.…”
Section: Spectroscopic Elementscontrasting
confidence: 99%
“…Finally, we note that if the light center velocities are applied without corrections, both semiamplitudes become 1.1 km s −1 smaller than listed in Table 7, and the derived masses become about 0.03 M lower. Our results differ slightly from those by Rucinski et al (2003), K p = 160.11 ± 0.74 km s −1 , K s = 147.21 ± 0.63 km s −1 , and γ = −12.74 ± 0.46 km s −1 , and are more accurate.…”
Section: Spectroscopic Elementscontrasting
confidence: 99%
“…The results reveal that V410 Aur is an A-type contact binary with a deep degree of overcontact of 52:4% AE 6:2%. The photometric mass ratio of q sp ¼ 0:1428 AE 0:0026 agrees well with the spectroscopic mass ratio of q sp ¼ 0:144AE 0:013 ( Rucinski et al 2003). When reanalyzing the photometric solution for XY Boo, a total of 441 observations in the V band and 440 observations in the B band (Binnendijk 1971) were used.…”
Section: Photometric Solutionssupporting
confidence: 66%
“…Using spectroscopic elements for V410 Aur ( Rucinski et al 2003) and XY Boo ( McLean & Hilditch 1983), we (re)determined the absolute physical parameters for those two binaries and listed them in Table 9. Unfortunately, there exist much larger errors in the derivation of the absolute parameters for XY Boo due to much larger errors in the radial velocity amplitudes of K 1 and K 2 , which are up to 28.2% and 23.7%, respectively.…”
Section: The Absolute Parameters and The Mass Transfer Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Pantazis & Niarchos (1998) empirically determined the gravity darkening coefficient for V523 Cas to be 0:53 AE 0:02, which is very different from the theoretical value of 0.32 (Lucy 1967) for convective atmospheres. Further modeling and the publication of new, high-precision radial velocity curves by Rucinski et al (2003) have shown that this departure was not needed, as we show with the simultaneous solution presented in this paper.…”
Section: Introductionmentioning
confidence: 57%